PROBIOTICS: THE UNDERVALUED CONQUERORS - Kawatra, Pallavi; Aiyappa, Cuckoo (Asian Journal of Pharmaceutical and Clinical Research, 2015)
ABSTRACT Probiotics or beneficial microorganismsâ€ have recently acquired the status of blockbusters in the pharmaceutical industry. Despite being commercially available, little is known about the magnitude to which they can contribute to various disease conditions such as inflammatory bowel disease, allergy, immunity, etc. this review dwells into the various mechanisms of actions of probiotics and summarizes the numerous benefits of these daily used products, including the recent advances. It also emphasizes on the possible unfavorable consequences, which can result due to their extensive use. Keywords: Probiotics, Allergy, Immunity, Inflammatory bowel disease.